Anticoagulant activity of a unique sulfated pyranosic (1→3)-β-L- arabinan through direct interaction with thrombin - Fernández, P.V. (2013)
A highly sulfated 3-linked β-arabinan (Ab1) with arabinose in the pyranose form was obtained from green seaweed Codium vermilara (Bryopsidales). It comprised major amounts of units sulfated on C-2 and C-4 and constitutes the first polysaccharide of this type isolated in the pure form and fully characterized. Ab1 showed anticoagulant activity by global coagulation tests. Less sulfated arabinans obtained from the same seaweed have less or no activity. Ab1 exerts its activity through direct and indirect (antithrombin- and heparin cofactor II-mediated) inhibition of thrombin. Direct thrombin inhibition was studied in detail. By native PAGE, it was possible to detect formation of a complex between Ab1 and human thrombin (HT). Ab1 binding to HT was measured by fluorescence spectroscopy. CD spectra of the Ab1 complex suggested that ligand binding induced a small conformational change on HT. Ab1-thrombin interactions were studied by molecular dynamic simulations using the persulfated octasaccharide as model compound. Most carbohydrate-protein contacts would occur by interaction of sulfate groups with basic amino acid residues on the surface of the enzyme, more than 60% of them being performed by the exosite 2-composing residues. In these interactions, the sulfate groups on C-2 were shown to interact more intensely with the thrombin structure. In contrast, the disulfated oligosaccharide does not promote major conformational modifications at the catalytic site when complexed to exosite 1. These results show that this novel pyranosic sulfated arabinan Ab1 exerts its anticoagulant activity by a mechanism different from those found previously for other sulfated polysaccharides and glycosaminoglycans. © 2013 by The American Society for Biochemistry and Molecular Biology, Inc.